Monocyte and M1 Macrophage-induced Barrier Defect Contributes to Chronic Intestinal Inflammation in IBD. Issue 6 (June 2015) - Lissner, Donata; Schumann, Michael; Batra, Arvind; Kredel, Lea-Isabel; Kühl, Anja A.; Erben, Ulrike; May, Claudia; Schulzke, Jörg-Dieter; Siegmund, Britta
Abstract : Background: Macrophages are key players in inflammatory bowel diseases (IBD). This study aimed to determine site-specific effects of defined macrophage subtypes on the integrity of the intestinal epithelial barrier. Methods: Macrophage subtypes in situ in intestinal specimens of patients with IBD were visualized by immunohistochemistry. In vitro polarization of human peripheral CD14 + cells yielded M1 or M2 macrophages. The influence of primary monocytes or macrophage subtypes on epithelial barrier integrity was analyzed by transepithelial resistance measurements, Western blot analysis, confocal laser scanning microscopy, and cytometric bead array in a coculture model of primary human macrophages and layers of intestinal epithelial cell lines. Results: The lamina propria of the inflamed intestine in patients with IBD, predominantly in Crohn's disease, is massively infiltrated by CD68 + cells also positive for inducible nitric oxide synthase and tumor necrosis factor (TNF) α. The presence of M1 macrophage shifted the balance in the local macrophage compartment towards a proinflammatory state. In the coculture model, monocytes and M1 macrophages reduced transepithelial resistance as a marker for epithelial barrier integrity. The mechanisms for paracellular leakage included intracellular relocalization of tight junction proteins like claudin-2 and epithelial cell apoptosis. Determined by specific cytokine blockade, M1 macrophages exerted their deleterious effect mainly through TNF-α, whereas monocyte-mediated damage was driven by the inflammasome effector cytokines, interleukin-1β and interleukin-18. Conclusions: Lamina propria monocytes and M1 macrophages invading intestinal tissues directly contribute to disrupting the epithelial barrier through deregulation of tight junction proteins and induction of epithelial cell apoptosis, thus driving intestinal inflammation in IBD. Abstract : Article first published online 21 April 2015.Supplemental Digital Content is Available in the Text.